Non-Iberian immigrant contribution to the viticulture and wine production in the South Region of Brazil: case of the Germans - Gama, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The purpose of this study was to analyze, recognize and rescue the non-Iberian immigrants’ role in the development of Brazilian viticulture and wine production, mainly in South Region of Brazil, rewriting the historical narrative. To reach this objective, in the first place, was made an analyze of German immigration process, focusing on those who expanded this agroindustry activity, geolocating the initial colonial productive areas. As methodology was analyzed a specialized literature bibliography, maps and records of historical research. German settlers didn´t employed slave labor. Despite not having remaining and not getting the same progress as Italian immigrants, was verified that, on the state of Rio Grande do Sul, German had implemented vineyards and wineries since the beginning of their colonization, sponsoring and helping the Italian immigrants who arrived, in Brazil, fifty years late, that was fundamental to the development of this beginning agroindustry activity. They provided logistic support, tools, grapes seedings and stay. Italian immigration was the main vector of Brazilian winemaking diffusion modernization, building the only consolidated wine-growing region: Serra Gaúcha. However, the current level of the wine quality that Brazil had reached, presents their precedents and precursors that must be rescued and recognized. In second place, was researched data survey of the traditional and modern wine production areas in the state of Santa Catarina that received non-Iberian immigrants, that is, IP South Coast and IP Santa Catarina Plateau were highlighted. Under the globalization process it is important to face competitors, fighting for local Geographic Indication as competitiveness strategy. Keywords: geographic indication; German immigration; non-Iberian immigration; south region of Brazil; terroir; viticulture/wine production